Viruses from understanding to investigation - Payne, Susan (Boston, MA Elsevier, 2017)
Viruses: From Understanding to Investigation provides students with a map for lifetime learning by presenting the definition and unique characteristics of viruses, including major topics, such as the virus lifecycle, structure, taxonomy, evolution, history, host-virus interactions and methods to study viruses. In addition, the book assesses the connections between, and among, the aforementioned topics, providing an integrated approach and in-depth understanding of how viruses work.--Provided by publisher.
1. A brief introduction to virology -- 2. The virus replication cycle -- 3. Virus structure -- 4. How we study viruses -- 5. Molecular and cell biology of the eukaryotic cell -- 6. Virus interactions with the host -- 7. Antiviral responses -- 8. An introduction to RNA viruses -- 9. Picornaviridae -- 10. Caliciviridae -- 11. Flaviviridae and Togaviridae -- 12. Order Nidovirales -- 13. Order Mononegavirales -- 14. Bunyaviridae -- 15. Arenaviridae -- 16. Orthomyxoviridae -- 17. Reoviridae -- 18. Introduction to DNA viruses -- 19. Poxviridae -- 20. Circoviridae -- 21. Parvoviridae -- 22. Papillomaviridae -- 23. Polyomaviridae -- 24. Adenoviridae -- 25. Herpesviridae -- 26. Viruses that use reverse transcription -- 27. The human hepatitis viruses -- 28. Evolution and genetics of viruses -- 29. Immune responses to viruses -- 30. Vaccines: Principles and approaches -- 31. Antiviral drugs and treatment strategies -- 32. Viral vectors and gene thereapy -- Appendix 1. The viruses we know -- lists, tables of taxonomy -- Appendix 2. Biochemical methods to study viruses -- analyzing proteins and nucleic acids -- Appendix 3. Tables describing morbidity and mortality (WHO) -- Appendix 4. Glossary
Keywords: Electronic books; Viruses